Evolution of studies about holocentric chromosomes: a literature review (Research, Society and Development, 2022)
The main source of study of cytogenetics is the chromosome, which is a cellular structure composed of genetic material and proteins. Chromosomes can be divided into holocentric chromosomes, which are chromosomes that do not have centromeres located along their structure, unlike monocentric chromosomes, which have a localized centromere, which is the most common type of chromosome in species in general. The present study sought to bibliographically review studies about holocentric chromosomes in order to follow the evolution of research on this topic. The literature review was carried out from bibliographic data on search engines such as Google Scholar, Scielo, PubMed and Lilacs. A total of 5,024 scientific articles were found, of which only ten were arranged in a table according to the criteria of the methodology. Although there are a lot of studies about holocentric chromosomes, more research is needed to clarify some evolutionary doubts, speciation of species and taxonomic comparisons between species of the same genus.